Two-step microalgal (Coelastrella sp.) treatment of raw piggery wastewater resulting in higher lipid and triacylglycerol levels for possible production of higher-quality biodiesel. (July 2021) - Lee, Sang-Ah; Ko, So-Ra; Lee, Nakyeong; Lee, Jun-Woo; Le, Ve Van; Oh, Hee-Mock; Ahn, Chi-Yong
Graphical abstract: Highlights: Two-step piggery wastewater treatment was optimized by single alga, Coelastrella sp. Lipid and triacylglycerol were largely accumulated at high ammonia concentration. Fatty acid profiles changed to higher MUFA/SFA for better biodiesel quality. Improved 4-day process removed 99, 92, and 100% of ammonia, COD, and phosphorus. Abstract: Microalgal treatment of undiluted raw piggery wastewater is challenging due to ammonia toxicity and a deep dark color hampering photosynthesis. To overcome these problems, (1) a microalga ( Coelastrella sp.) was isolated from an ammonia-rich environment, (2) the wastewater treatment was divided into two steps: a heterotrophic process followed by a mixotrophic process, and (3) a narrower transparent photobioreactor was employed with higher light intensity in the mixotrophic process. Coelastrella sp. removed 99% of ammonia, 92% of chemical oxygen demand (COD), and 100% of phosphorus during the 4-day process. Acetate in the wastewater relieved the ammonia stress on microalgae and promoted algal lipid and triacylglycerol productivity. Oxidative stability and low-temperature fluidity of triacylglycerols in lipids were improved by means of an altered fatty acid profile. Aside from the overall microalgal treatment performance, the proposed processing of piggery wastewater yielded a material suitable for possible production of algal biodiesel of better quality.